FICTIONAL PECULIARITIES OF VSEVOLOD NESTAIKO’S PROSE FOR CHILDREN (ON THE BASIS OF THE NOVEL “TOREADORY Z VASIUKIVKY”) - Lytvyn, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article examines the issue of peculiarities of the authorial style. The principal attention is focused on compositional, landscape, pedagogic characteristics. The problem of creating images in the trilogy by Vsevolod Nestaiko takes an important place.